Accounting for the Size of Nations: Empirical Determinants of Secessions and the Soviet Breakup - Marvin Suesse (European Historical Economics Society (EHES), 2014)
Little is known about the empirical determinants of secessions, despite a rich theoretical literature on the subject. Economic theory predicts that the incentive to secede should be determined by the size of the seceding province, as well as preference heterogeneity, income inequality, the extent of democratization, and trade potential. This paper tests these assertions by treating the dissolution of the Soviet Union as a historical experiment in state breakup. I exploit regional variation in pro-secessionist protests across the 184 provinces of the Union to approximate the varying demand for secession. I find strong evidence for the existence of a trade-off between size and heterogeneity in shaping demand for secession, whereas other factors receive only qualified support. Finally, I demonstrate that the factors determining popular demand for secession are only weakly related to the extent to which local elites actually pursue a secessionist policy.
Keywords: H40; H71; 330